2020
DOI: 10.1021/acssuschemeng.0c05845
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Tailored Silicon Nanoparticles with Ultrahigh Fluorescence and Photostability for Cellular Imaging

Abstract: Until now, the green and facile synthesis of highly fluorescent silicon nanoparticles (SiNPs) with robust luminescent stability and favorable biocompatibility for cellular imaging is still a challenge. Here, a novel biomimetic strategy is demonstrated for the preparation of cell-tailored fluorescent SiNPs by the effective reaction of the easily available and operable yeast secretion and silicon precursor, K2SiF6. The as-prepared SiNPs exhibit excellent water dispersibility, favorable biocompatibility, and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…59 In 2020, Cui et al utilized the extracellular secretion of yeast cells to react with an inorganic silicon source K 2 SiF 6 to obtain blue-emitting Si QDs with a PL QY of 44.77%. 60 The extracellular secretion of yeast cells can act as reductants and stabilizers in the biomimetic synthesis process. However, due to the complexity of biological systems and the lack of research on related mechanisms, the operability of the biomimetic method is still weak compared to those of traditional methods.…”
Section: ■ Synthesis Of Si Qdsmentioning
confidence: 99%
See 1 more Smart Citation
“…59 In 2020, Cui et al utilized the extracellular secretion of yeast cells to react with an inorganic silicon source K 2 SiF 6 to obtain blue-emitting Si QDs with a PL QY of 44.77%. 60 The extracellular secretion of yeast cells can act as reductants and stabilizers in the biomimetic synthesis process. However, due to the complexity of biological systems and the lack of research on related mechanisms, the operability of the biomimetic method is still weak compared to those of traditional methods.…”
Section: ■ Synthesis Of Si Qdsmentioning
confidence: 99%
“…As reported in Wu’s work, silica-rich diatoms can be used as natural biomass silicon precursors for the microwave-assisted biomimetic synthesis of red-emitting Si QDs with narrow fwhm (∼30 nm) . In 2020, Cui et al utilized the extracellular secretion of yeast cells to react with an inorganic silicon source K 2 SiF 6 to obtain blue-emitting Si QDs with a PL QY of 44.77% . The extracellular secretion of yeast cells can act as reductants and stabilizers in the biomimetic synthesis process.…”
Section: Synthesis Of Si Qdsmentioning
confidence: 99%
“…On the other hand, PSiNPs can be employed as imaging CAs without being labeled with fluorescent dyes or quantum dots because PSi itself possesses tunable photoluminescence in the range from visible light to NIR [34] . In addition, the photoluminescence of PSiNPs is more stable than the fluorescence from dyes, which can easily be photobleached [34a,35] . The Zabotnov group used picosecond laser ablation of porous silicon films and nanowires to synthesize small silicon nanoparticles (14–65 nm), which have fluorescence emission in the NIR range (600–1000 nm) and created a new prospect used as optical imaging contrast agents [32] .…”
Section: Imaging Modelsmentioning
confidence: 99%
“…33−36 SiNPs with excellent biocompatibility have also been successfully applied in cell imaging and cell tracking. 37,38 The above reports indicated that SiNPs have excellent application potential in the field of analytical detection. So far, the fluorescence method based on SiNPs for VB 2 detection has not been reported.…”
Section: Introductionmentioning
confidence: 97%